Reclamation and Post-Mining Management at PT. XYZ East Kalimantan Province - Vico, Julyas; Sibarani, Mentiana (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
East Kalimantan Province is one of the largest coal producers in Indonesia. Mining activities often have a negative impact on the environment, making it important to manage reclamation effectively. The purpose of this study is to understand and analyze the management of reclamation and post-mining at PT XYZ to minimize the negative impacts of mining activities. This research uses a case study method with a qualitative descriptive approach. Data was collected through interviews, observation and documentation. The informants involved were purposively selected to gain an in-depth understanding of reclamation practices. The results show that PT XYZ routinely conducts reclamation and post-mining activities. However, the implementation has not been fully optimized due to various constraints, including the lack of a good reclamation plan, adequate funding and the involvement of all relevant parties. To minimize the negative impacts of mining activities, a strong commitment from the company, community and government is needed to create sustainable and environmentally friendly mining operations. This study provides important insights into reclamation practices and managerial approaches that can be adopted by other companies.